Safety property attributes in critical systems for requirement specification : A review - Azma, Abdullah; Rohani, Abu Bakar; Gunaratnam, Kiriyadhatshini; Hujainah, Fadhl; Mohd Fairus, Abdul Farid (Institute of Electrical and Electronics Engineers Inc., 2023)
The integration of critical system components, requirement specification, and safety properties plays a crucial role in advancing the development and verification processes of critical systems. This integration enables effective analysis, management of safety requirements, and identification of potential risks. Although several studies have explored safety properties in safety analysis (SA), they often lack a comprehensive presentation of all possible safety properties with proper categorization. This paper aims to address this gap by analyzing a comprehensive list of possible safety properties in requirement specification. The list is derived through an extensive analysis of studies published between 2019 and 2023, with a focus on past researchers' contributions. Additionally, our future work includes a systematic literature review encompassing a broader range of studies to further enhance the analysis. By providing a structured approach for addressing safety aspects, this paper contributes valuable insights into the significance of safety properties in ensuring the safety and reliability of critical systems. It lays the foundation for improved safety analysis (SA) practices and strengthens the overall development process of critical systems.